BOOSTER EMPLOYEE PERFORMANCE: A CASE STUDY ON PT. HOU TECH INDONESIA - Yogatama, Ahmad Nizar; Arsita, Nia; Ikrima, Sailil (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
PT. Hou Tech Indonesia as one of the companies engaged in the wood panel industry that still survives in the disruptive era knows very well that the quality and reputation that it has owned is inseparable from the role of the workforce, but is currently facing a decline in performance that was allegedly derived from increased attendance rate. Researchers feel the need to reassess how the right decision for PT. Hou Tech Indonesia in order to be able to maintain and improve the performance of employees in the production department. The purpose of this study is how to make the right decision for PT. Hou Tech Indonesia in order to be able to maintain and improve the performance of employees in the production department. The study took a population and sample of all employees of the production department of PT. Hou Tech Indonesia with a total of 108 employees using a simple random sampling technique that is all employees of the production section at PT. Hou Tech Indonesia, which is willing to provide all the information researchers need. Primary data collected by researchers was conducted through a questionnaire using a 5-point Likert scale and analyzed using multiple linear regression analysis. The results showed that increasing employee commitment is the best option so that the production performance of employees would increase.